Evaluation of an alternative household water treatment system based on slow filtration and solar disinfection. (24th November 2021) - Rosa e Silva, Guilherme Otávio; Loureiro, Helen Oliveira; Soares, Laura Guimarães; de Andrade, Laura Hamdan; Santos, Rana Gabriela Lacerda
Abstract: Drinking water consumption is essential to maintain a good quality of life, but it is not available for all communities. Therefore, this work aimed to develop an alternative and accessible process for water treatment, based on filtration and solar disinfection, and evaluate it in both bench and pilot scales. The construction cost of the system was estimated and compared with other available options so that its economic viability could be discussed. For this purpose, water from a stream was collected and analyzed. A filter made of PVC tubes, sand, and gravel was built, acting, respectively, as a column, filtering medium, and support layer. As for the disinfection process, the SODIS (Solar Water Disinfection) methodology was adopted. The water was exposed to the sun, and the best exposure time was determined based on the analysis of total coliforms and E. coli . Finally, a prototype was built for a flow rate of 37.5 L d −1, consisting of two filters operating at a filtration rate of 2.38 m 3 m −2 d −1 . About 97% turbidity removal was obtained, as well as 99.9% for total coliforms and 99.1% for E. coli . It is estimated that the cost of building a water treatment system for one person is approximately USD 29.00. HIGHLIGHTS: On pilot-scale tests, slow filtration showed high efficiency on bacteria removal, which indicates that a biological layer was formed during the operation. The SODIS treated water should be stored at a low temperature or used as soon as possible, due to the bacteria regrowth process that can occur overnight. The system costs around 116 USD for a four-people house, which is considered affordable for low-income families. Graphical Abstract